Engagement with AI in teacher education—discourses, processes of domestication and dynamics of transformation - Storm-Mathisen, Ardis; Giæver, Tonje Hilde; Helle-Valle, Jo; Engen, Bård Ketil; Karstensen, Steinar (Frontiers in Education, 2026)
The public introduction of ChatGPT in 2022 marked a turning point in mainstream awareness of artificial intelligence (AI), catalyzing widespread debates on what it was, what it could be used for and how this would alter our world. In the domain of higher education, AI was framed as a transformative tool for knowledge production and pedagogical innovation, contingent on users’ critical technological awareness and competence. This study explores how AI was introduced, interpreted, and acted upon within a teacher education context in the aftermath of the ChatGPT release. It takes the authors’ own university faculty and an interdisciplinary digitalization network as its case and employs a methodology that combines a reflexive and autoethnographic approach with document and survey data analysis. By way of using discourse, domestication and social mechanisms as analytical concepts we identify central events, arguments and controversies in the larger context and discuss local ‘taming’ processes and dynamics. Our findings highlight both opportunities and challenges in integrating AI into teacher education. While the introduction of AI did set in motion transformations of established practices, it varied how these transformations were understood and reacted upon. When AI increasingly became ingrained and automated in teacher educators work technology, lack of institutional strategies to guide AI use in teacher educator practices individualized responsibilities and diversified orientations to and applications of AI in pedagogical processes. In this situation bottom-up organized discussion networks among colleagues from different teacher educator departments and subject fields scaffolded reflexive and transformative discussions and engagements with AI, as a context where taken-for granted knowledge and perspectives about these emergent technologies could be opened, vocalized, experimented with and challenged.